A multi-centre observational cohort study on pharmacogenomic predictors of rosuvastatin discontinuation in a multiethnic population - Alqasrawi, Mais N.; Al-Mahayri, Zeina N.; Khasawneh, Lubna Q.; AlBawa’neh, Areej S.; Dabaghie, Lilas; Altoum, Sahar M.; Hamza, Dana; Aburuz, Salahdein; Misra, Virendra; Jamil, Gohar; Ouda, Husam; Al-Bakshy, Faiz; et al. (Frontiers in Pharmacology, 2025)
BackgroundRosuvastatin is widely used for cardiovascular risk reduction, but treatment discontinuation limits its long-term benefit. Genetic variants, particularly in ABCG2 and SLCO1B1, influence rosuvastatin’s transport, efficacy, and tolerability. The ABCG2 rs2231142 variant is associated with enhanced efficacy due to increased systemic exposure; however, it also raises the risk of adverse effects, especially muscle-related symptoms. Evaluating the impact of these variants in a real-world, multiethnic population is essential to improving adherence and guiding personalized therapy. The aim of this study is to investigate the influence of ABCG2 rs2231142 (G>T; Q141K) and SLCO1B1 rs4149056 (T>C; V174A) variants on rosuvastatin discontinuation and LDL cholesterol changes in a multiethnic population in the United Arab Emirates (UAE).MethodsIn this multicenter prospective cohort study, 422 adults prescribed rosuvastatin were followed for 12 months. Discontinuation data were collected from records or phone calls. Genotyping was performed using TaqMan SNP assays. Cox regression and Kaplan-Meier analyses assessed discontinuation risk by genotype; LDL changes were analyzed using descriptive statistics and logistic regression.ResultsThe ABCG2 rs2231142 T/T genotype had the highest risk of discontinuation (HR = 4.40, p < 0.001), followed by G/T (HR = 1.75). LDL change differed significantly between continuers (−17.86%) and discontinuers (+21.89%) (p < 0.001). The ABCG2 variant was more frequent among discontinuers (30.6% vs. 17.4%, p = 0.0026). SLCO1B1 rs4149056 was not associated with discontinuation.ConclusionMinor allele carriers are at higher risk of discontinuation due to adverse effects. Genetic testing for ABCG2 may support personalized rosuvastatin therapy and improve adherence.